Rocks and Minerals; A Guide to Familiar Minerals, Gems, Ores, and Rocks - Zim, Herbert S. and Shaffer, Paul R.; Illustrated by Perlman, Raymond (New York Golden Press, 1957)
Includes information on collecting and identifying minerals, and sections on metallic, nonmetallic, gem and rock-forming minerals, and on igneous, sedimentary and metamorphic rocks.
Include colour illustrations and index
Keywords: Mineralogy -- Petrology -- Rocks